2017
DOI: 10.1007/s12098-017-2363-8
|View full text |Cite
|
Sign up to set email alerts
|

Need for Different Cutoff Values for Reading Mantoux Test with 2TU and 5TU PPD

Abstract: Cutaneous hypersensitivity to 2TU PPD is not comparable to that of 5TU PPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Also the results vary with different strengths of PPD used for TST. Studies from India have shown that cutaneous hypersensitivity to 1TU or 2TU PPD or 5TU PPD are not comparable [ 16 , 17 ]. However a study from Philippines on TST reactivity among children with TB, found 2 TU PPD RT-23 to be comparable with 5 TU PPD-S and that one can be used instead of the other in routine Mantoux testing [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also the results vary with different strengths of PPD used for TST. Studies from India have shown that cutaneous hypersensitivity to 1TU or 2TU PPD or 5TU PPD are not comparable [ 16 , 17 ]. However a study from Philippines on TST reactivity among children with TB, found 2 TU PPD RT-23 to be comparable with 5 TU PPD-S and that one can be used instead of the other in routine Mantoux testing [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that Mantoux reaction was significantly higher at 72 h compared to the reaction at 48 h. They came to conclusion that in clinical practice, Mantoux test should be read at 72 h as readings at 48 h may underestimate the size of the reaction. [8] Lee and Oh indicated that a new criteria for tuberculin reactivity to 2 TU are to be established in future studies. [4] In a study by Ramaraj et al, authors proposed a formula to make the reactions of 5 TU comparable to that of 2 TU which is, 5 TU = 2 TU × 0.9 + 2.82.…”
Section: Discussionmentioning
confidence: 99%
“…They also had an opinion that further studies with a larger sample size and positive cases were required to recommend this formula for the population and the same cutoff of 10 mm or more is not applicable to both 5 TU and 2 TU strength of PPD. [8]…”
Section: Discussionmentioning
confidence: 99%